Employee Satisfaction Mediates Motivation and Discipline Commitment at the Sidoarjo Regional Civil Service Agency: Kepuasan Pegawai Memediasi Motivasi dan Disiplin Keterikatan BKD Sidoarjo - Kautsarina, Raisa; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background High employee engagement is essential for sustainable organizational performance, particularly within public service bodies. Specific Background This study investigates how employee welfare, motivation, and discipline contribute to employee engagement at the Regional Civil Service Agency (BKD) of Sidoarjo, using employee satisfaction as a key mediating factor. Knowledge Gap National survey results show ASN engagement in East Java remains at the 'good' category (13.10%), indicating a need to identify the precise mechanisms that convert internal factors (motivation/discipline) and external factors (welfare) into engagement. Aims To analyze the direct and indirect relationships of welfare, motivation, and discipline on employee engagement, mediated by employee satisfaction. Results Statistical testing reveals that welfare has a significant direct relationship with engagement. In contrast, motivation and discipline do not directly relate to engagement but successfully achieve it only through the full mediation of employee satisfaction. Novelty This research demonstrates that satisfaction acts as a prerequisite pathway for motivation and discipline to materialize as engagement in the BKD Sidoarjo context. Implications Management efforts should prioritize fostering high employee satisfaction before expecting direct results from motivation and discipline programs. Highlights: Motivation and discipline require satisfaction for employee engagement. Welfare shows a direct link to employee engagement. Employee satisfaction is a full mediator for two out of three variables. Keywords: Employee Welfare, Motivation, Employee Discipline, Employee Engagement, Employee Satisfaction